Central America urgently needs to reduce the growing adaptation gap to climate change - Ley, Débora; Guillén Bolaños, Tania; Castaneda, Antonethe; Hidalgo, Hugo G.; Girot Pignot, Pascal O.; Fernández, Rodrigo; Alfaro, Eric J.; Castellanos, Edwin J. (Frontiers in Climate, 2023)
Central America is highly impacted by current extreme events associated with climate variability and the adverse effects of climate change, showing high vulnerability compounded by its historical context and socio-economic structure. In the light of the important findings published by the WGII of the IPCC AR6 in 2022 on the adverse effects of climate change on the Central America region, there is still a clear need to improve data availability and increase the number of studies on projections of changes in the climate, risks, impacts, vulnerability and adaptation from the region to inform decision-makers and practitioners. The region has seen an increase in the number of adaptation projects implemented; however, there is limited information about their success or failure and there are few case studies and reviews of lessons learnt, highlighting an important gap in the implementation of effective adaptation measures. This paper presents a current review of the literature on climatology, hydrology, impacts and vulnerability, mitigation and adaptation responses, action plans and potential losses and damages in the region. It also proposes actionable recommendations based on the main gaps found and presents a case study of the Central American Dry Corridor, one of the climate change and underdevelopment hotspots of the region. We finish with a discussion highlighting the importance of considering system transitions perspectives, as well as the need to plan and implement more transformational adaptation approaches to reduce further losses and damages and to further address adaptation gaps in Central America.